Navigating the tension: Islamic value and digital transformation in Pakistani educational management - Hussain, Mujahid (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
This study investigates how educational management is practiced within Islamic institutions by integrating conceptual analysis with qualitative field data from selected madrasas and Islamic universities in Pakistan. Although educational management in Islamic institutions has been widely discussed theoretically, there remains a lack of empirical studies that examine how administrators and teachers actually implement Islamic values in day-to-day management practices, which creates an important gap in the literature. Drawing on qualitative multiple-case study, data were gathered through semi-structured interviews with administrators (n = 12) and teachers (n = 18) and supported by a review of institutional documents. The study explores how values such as amanah, shūrā, and ihsan shape leadership behaviour, curriculum decisions, and responses to digital transformation. Thematic analysis reveals that management processes often rely on traditional authority structures and limited strategic planning, and that digital innovation is acknowledged as important yet constrained by inadequate resources. Participants also expressed the ongoing tension between preserving religious authenticity and meeting modern educational demands. Overall, the findings highlight the need for a professionalized and ethically grounded management model that reflects Islamic principles while responding effectively to contemporary educational challenges, and the study proposes an integrated leadership framework to support institutional sustainability and innovation.